2012
DOI: 10.5005/jp-journals-10005-1149
|View full text |Cite
|
Sign up to set email alerts
|

Mutans Streptococci Colonization in Relation to Feeding Practices, Age and the Number of Teeth in 6 to 30-Month-Old Children: Anin vivoStudy

Abstract: Background: Early childhood caries has been characterized as first affecting the primary maxillary anterior teeth, followed by the involvement of the primary molars. Other terms for dental caries in preschool children, which inappropriately may imply cause for the disease, includes baby bottle tooth decay, nursing caries, milk bottle syndrome, baby bottle caries, nursing bottle mouth and nursing mouth.Aim: To explore the relationships of feeding practices, age and number of teeth present with mutans streptococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 96 publications
0
5
0
1
Order By: Relevance
“…In studies reported, breastfeeding ranged from 5 to 100%. 11 14 18 19 28 31 33 37 - 39 Bottle-feeding was widely prevalent in most of the studies ranging from 51 to 97.9%, 13 17 21 22 38 40 - 43 whereas maximum mixed feeding (both breast and bottle-feeding) was found in some studies, ranging from 19 to 42.6%. 20 27 32 35 44 …”
Section: Discussionmentioning
confidence: 99%
“…In studies reported, breastfeeding ranged from 5 to 100%. 11 14 18 19 28 31 33 37 - 39 Bottle-feeding was widely prevalent in most of the studies ranging from 51 to 97.9%, 13 17 21 22 38 40 - 43 whereas maximum mixed feeding (both breast and bottle-feeding) was found in some studies, ranging from 19 to 42.6%. 20 27 32 35 44 …”
Section: Discussionmentioning
confidence: 99%
“…S.mutans colonize the surface of teeth and soft tissues, and will be the cause of disease in the oral cavity. 3,5 Carbohydrates-contained in breast or formula milk have aglycolysis process that will result in fermentation reactions and cause acid pH. This is what triggers the growth of bacteria, particularly S. mutans which were mostly found in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…This is what triggers the growth of bacteria, particularly S. mutans which were mostly found in the oral cavity. 5 The measuring tool in this research was colony form unit, a method used to calculate the number of colonies of S.mutans. The validity and reliability of this measurement has been tested and has been frequently used in research settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations